Content English integrated mathematics learning with reduced split attention: a cognitive load approach - Iskandar Iskandar; Metria Dicky Putra; cAmon Bernabas Tenis (IRecall Journal, 2026)
Integrating English into mathematics learning may increase students’ cognitive load, particularly when instructional materials require learners to divide their attention between multiple sources of information. Based on Cognitive Load Theory, instructional materials designed using Reduced Split Attention are expected to minimize unnecessary cognitive processing. This study aimed to reduce students’ cognitive load through the implementation of Content and English Integrated Mathematics Learning with Reduced Split Attention. This study employed Classroom Action Research conducted in two cycles consisting of planning, action, observation, and reflection stages. The participants were eleventh-grade students in a public senior high school. Data were collected using a mental effort rating scale to measure students’ cognitive load during mathematics learning. The data were analyzed descriptively by comparing cognitive load scores in the pre-cycle, Cycle I, and Cycle II. The results showed a consistent decrease in students’ cognitive load across the three stages. The mean cognitive load score in the pre-cycle was 6.10, which decreased to 4.35 in Cycle I and further decreased to 2.95 in Cycle II. The reduction in cognitive load indicates that the implementation of Reduced Split Attention successfully minimized unnecessary cognitive processing. Improvements made in Cycle II, including clearer integration of formulas, explanations, and English terminology, further reduced students’ mental effort during learning. These findings indicate that Content and English Integrated Mathematics Learning with Reduced Split Attention effectively reduces students’ cognitive load. The results suggest that well-integrated instructional materials play an important role in supporting cognitively efficient mathematics learning.